An Early Ordovician (late Tremadocian) bivalve fauna from Iran. (19th July 2019) - Cope, John C.W.; Ghobadi Pour, Mansoureh
Abstract : A small bivalve fauna is described from the late Tremadocian of Iran, adding to the very few localities in the world where bivalves of this age are known. In addition to indeterminate praenuculids, the fauna includes the praenuculid Pensarnia and the pteriomorphian genus Glyptarca . The former is otherwise known from South Wales and the latter, from South and Mid‐Wales and West Yunnan, China.